What Determinants Influence Students to Start Their Own Business? Empirical Evidence from United Arab Emirates Universities - Alexandrina Maria Pauceanu; Onise Alpenidze; Tudor Edu; Rodica Milena Zaharia (Sustainability, 2019)
What factors influence students to start their own business? What are the implications at the university level? This paper aims to answer to these questions and investigates, at a micro level (university), the motivation for entrepreneurial intentions among students in 10 universities from the United Arab Emirates (UAE). An online inquiry has been conducted among 500 students between April and June 2018, and 157 fully completed questionnaires were retained. Factor Analysis with Varimax (with Kaizer Normalization) rotation and logistic regression were used to identify what factors motivate students to start their own business and, from those factors, which one is determinant in this decision. Also, age and parental self-employment status were used to determine the influence of these factors. Four factors have been identified as determinants for students to start their own business: entrepreneurial confidence, entrepreneurial orientation, university support for entrepreneurship, and cultural support for entrepreneurship. Surprisingly, the only factor significantly correlated with the intention in starting a business is entrepreneurial confidence. This factor becomes even stronger when it is associated with age (20-25 years old) and parents' self-employment status. These conclusions involve specific challenges on the university level, related to the role of entrepreneurial education and on country level, in link with the effectiveness of governmental programs to enhance entrepreneurial endeavours. Further research can explore and test these findings on a representative sample for the UAE, and for other countries
Keywords: 330; entrepreneurship; entrepreneurial intentions; determinants of entrepreneurship; entrepreneurship education; entrepreneurial confidence; United Arab Emirates